“What’s left of the father?” On the sidelines of the Constitutional Court’s decision on the withdrawal of consent to MAR by the ex partner (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
In its judgment n. 161/2023, the Constitutional Court declared unfounded the question of the legitimacy of art. 6, par. 3, of Law No. 40 of 2004, in the part in which it does not provide for the revocation of the consent given by man after the fertilization of the egg but before the implantation of the embryo. Although the legal context in which the provision currently stands has changed radically, the judge of laws has considered that the balancing of constitutional interests defined therein is not unreasonable. The article critically examines the arguments in support of the decision, reflecting in particular on the paternity and possible slippages that could result from an "emotional" reading of the judgment.
Keywords: Medically Assisted Reproduction; informed consent; freedom and responsibility; paternity; rights of the unborn